RETRACTED: Innovations in Public Financial Reporting Systems to Increase Accountability and Transparency - Fakhrurrazi; Zikkir Rachman; Kumba Digdowiseiso (Journal of Social Science)
This journal discusses the innovation in the public financial reporting system to enhance accountability and transparency. In the digital era, technological innovations such as Fintech, e-procurement, e-budgeting, and e-audit have influenced the public financial reporting system, making it more accessible and understandable. The journal emphasizes the importance of transparency and accountability in the public financial reporting system, and how innovation can help achieve these goals. This research uses a qualitative approach and collects data from various credible online sources.